PELESTARIAN TARI JOGET SONDE SANGGAR RIZA MANDAU DI KOTA DURI PROVINSI RIAU - Aznel, Maharani; Susmiarti (Universitas Negeri Padang, 2026)
Sonde Dance at the Riza Mandau Studio. The type of research used is qualitative research with a descriptive method. The research instrument is the researcher themselves, assisted by writing tools and a camera. Data is collected through literature studies, observation, interviews and documentation. The steps in analysing the data are data collection, data reduction, data presentation, and drawing conclusions. The research results show that the preservation strategy of the Sonde Dance implemented by the Riza Mandau Studio is carried out through two main approaches, namely internal preservation and external preservation. The internal preservation strategy is realised through regular coaching and training activities for studio members, especially the younger generation. In this process, the instructor not only teaches dance movement techniques but also instills the cultural values contained in the Joget Sonde Dance. In addition, internal preservation is also evident in efforts to maintain the authenticity of the dance form, the accompaniment of traditional music, and the interaction patterns within the performance. This activity demonstrates that the preservation strategy focuses on the process of cultural transmission directly from generation to generation within the studio environment. Meanwhile, the external preservation strategy is carried out through the studio's involvement in various activities outside the internal environment, such as performances in cultural events, festivals, and government activities, as well as collaboration with educational institutions and related agencies. Through this activity, the Joget Sonde dance is introduced to the wider community, thereby increasing its appreciation and existence amidst the developments of the times. Support from external parties also becomes an important factor in strengthening the sustainability of its preservation.